Vegetation Index and Dynamics - Cano Carmona, Eusebio; Cano Ortiz, Ana; Quinto Canas, Riocardo; Maria Musarella, Carmelo (IntechOpen, 2022)
The book contemplates different ways of approaching the study of vegetation as well as the type of indices to be used. However, all the works pursue the same objective: to know and interpret nature from different points of view, either through knowledge of nature in situ or the use of technology and mapping using satellite images. Chapters analyze the ecological parameters that affect vegetation, the species that make up plant communities, and the influence of humans on vegetation.